(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Europe has been a centre fortrade and commerce since ages. Industrial revolution in Europe has increasedthe competition among nation states within Europe. The Economies of Britain,Netherlands, Germany, France and Portugal have been competing with each other’sin markets of Far East and South America. Though movements of goods andservices have been a common feature among nation states within Europe a Commonintegrated market with regulatory mechanism is a recent phenomenon. In themiddle ages and early part of the 20th century the trade disputesamong different constituents have been resolved by bilateral treaties amongnation states and through arbitration and intervention of Chamber of Commerce,guilds in case of commercial disputes between two commercial entities. The multilateraltreaties to resolve trade and commercial disputes comes in picture in mid of 20thcentury when European Coal and Steel Community Treaty also known as Paristreaty was signed in 1951 it was followed by European Economic Treaty which wasmuch wider and cover all segment of trade and commerce. However the presentUnion of Europe or better known as European Union a Union of Member States ofEurope encompassing Economic and Political Union (to an extent) comes throughMaastricht Treaty in 1992. The provisions of Maastricht treaty were muchwidened by later day treaties of Amsterdam, Nice and Lisbon. Europe has for thefirst time a Parliament of its own, a Monetary Union giving birth to Euro asCommon currency, European Central Bank, Fiscal consolidation and free movementof trade and services. This all is regulated by European Union Law, whichincludes Trade laws through directives and regulations monitored by EuropeanCommission. Trade disputes among member states are resolving through DisputeSettlement Board (DSB). The trade disputes can be put in three categories oneamong member states within EU, secondly dispute between Member state of EU andNon Member states and third dispute arising out of non EU investor and Memberof EU where EU is signatory to multilateral treaty and provisions of which hasbeen violated by Member state. EU dispute settlement mechanism is largely basedon WTO provisions and provisions of GAAT. In this article a study has been doneon these disputes particularly where EU directives and Regulations are inconflict with Constitutional and Local Law of Member states.